Biosurfactants and its Applications in Aquaculture - Nadella, Ranjit Kumar; Muthulakshmi, T.; Minimol, V. A.; Murugadas, V.; Basha, K. A.; Joseph, Toms C.; Prasad, M. M. (Fishery Technology, 2020)
Aquatic environments harbour a wide diversity ofmicroorganisms that produce several novel compounds.Biosurfactant is a compound synthesizedby microorganisms which have distinct physiologicaland metabolic pathways. Structurally they areamphiphilic molecules with hydrophilic moiety(tail) and hydrophobic moiety (head) that accumulatesbetween two fluid phases and reduces surfacetension. The property of a particular biosurfactantmolecule is dependent on the location as well as thesize of the functional groups. These biosurfactantscan form strong emulsions at wide ranges of pH andtemperature. The physico-chemical and biologicalproperties are unique which makes the biosurfactantwidely applicable in different fields, includingaquaculture. Most common applications includeinhibition of quorum sensing mechanism of thebacterial communication and inhibiting the growthof pathogenic bacteria. In case of fish feed processingindustries, the emulsions formed by thebiosurfactant can be incorporated into diet. Themicelle forming property of the biosurfactant can beexploited for developing targeted drug deliverytechniques. The methodologies and techniques forscreening potential microorganisms which producebiosurfactant from aquatic environment and itsapplication in aquaculture sector assume greatimportance. This communication provides a detailedreview on the developments in these areas.